Self-regulation of Arabic Reading Comprehension of upper Elementary Students - Rania Abdo; 10.17398/1988-8430.31.229 (Tejuelo: Didáctica de la Lengua y la Literatura)
This study examines the self-regulation processes of reading comprehension in Arabic of Lebanese students in upper elementary who perform poorly only in this language. The focus is on the cognitive and metacognitive strategies these students use, and on the motivational components of self-regulation. A questionnaire and two different semi-structured interviews were administered to fifteen elementary students and to their Arabic teachers, in a French-speaking school in Beirut. Participants do not self-regulate efficiently their Arabic reading comprehension and they tend to seldom use cognitive learning strategies. Self-regulatory processes are predicted by participants’ lack of motivation that manifests itself mostly through perceptions of moderate self-efficacy of performance and low expectations of success. This is the first step towards understanding the learning processes of students poorly performing in Arabic reading. It can provide means that will help students in applying self-regulated content learning of not only texts in Arabic but readings in general.